1999
DOI: 10.1002/etc.5620180618
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicological assessment of solid wastes: A combined liquid‐ and solid‐phase testing approach using a battery of bioassays and biomarkers

Abstract: Abstract-Municipal solid waste incinerator bottom ash (MSWIBA) was used as a test matrix for comparing the responses of different variables (solid phase vs leachate media) through toxicity tests and resulting endpoints. Toxicity of leachate and solidphase MSWIBA was evaluated with three terrestrial plants, namely oats (Avena sativa L.), Chinese cabbage (Brassica campestris L. cv. chinensis), and lettuce (Lactuca sativa L.). Assessment endpoints for these plant tests were biomass fresh weight, germination rate,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0
11

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 33 publications
4
32
0
11
Order By: Relevance
“…Li et al [54] and Bakare et al [55] reported that the possible mechanism of municipal landfill and sludge leachates induced genotoxicity and toxicity in mice was by oxidative damage. Similarly, oxidative stress was implicated in incinerated bottom ash and municipal landfill leachates induced toxicity and genotoxicity in plant test systems [56][57][58]. These are in concert with our findings that e-waste leachate and contaminated well water induced elevated levels of lipid peroxidation and alterations in oxidative stress enzymes in liver of treated mice.…”
Section: Discussionsupporting
confidence: 88%
“…Li et al [54] and Bakare et al [55] reported that the possible mechanism of municipal landfill and sludge leachates induced genotoxicity and toxicity in mice was by oxidative damage. Similarly, oxidative stress was implicated in incinerated bottom ash and municipal landfill leachates induced toxicity and genotoxicity in plant test systems [56][57][58]. These are in concert with our findings that e-waste leachate and contaminated well water induced elevated levels of lipid peroxidation and alterations in oxidative stress enzymes in liver of treated mice.…”
Section: Discussionsupporting
confidence: 88%
“…Nickel, which has been found to be highly toxic, was also analysed in the sample at levels much higher than in control and maximum permissible limits for leachate discharged by regulatory bodies [17]. Nickel is known to penetrate cells rapidly and causes osmotic lyses of cells resulting in cell death [26].…”
Section: Discussionmentioning
confidence: 99%
“…Ten percent leachates were prepared from each of the three solid waste samples by inorganic-aqueous extraction using the French standard method [Ferrari et al, 1999], with minor modifications. Briefly, 100 g of solid waste were added to 1000 ml of demineralized water (w/v), and this mixture was shaken continuously for 24 hr at ambient room temperature (25 6 18C).…”
Section: Preparation Of Leachatesmentioning
confidence: 99%